DINAMIKA HUKUM KHAMR DALAM AL-QUR’AN: STUDI KOMPARATIF TAFSIR AHKAM AL-QUR’AN KARYA AL-JAṢṢĀṢ DAN IBNU AL-‘ARABI DALAM KONTEKS SOSIAL KONTEMPORER - Ahmad Ulil Albab; Ni’matulloh Al Jauhariyah (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2025)
This research examines the differences in legal interpretation methodology between Al-Jaṣṣāṣ and Ibn Al-'Arabi in understanding the verses about alcohol in the Qur'an, as well as its implications for the dynamics of Islamic law in the contemporary era. The background of this research is the need to understand how classical tafsir products can answer modern challenges, especially related to the use of alcohol in the pharmaceutical sector, food, and social regulation. This research uses a qualitative approach with a literature study method, comparatively examining the works of Ahkam Al-Qur'an of the two mufassirs. The results show that Al-Jaṣṣāṣ prioritizes a rational approach with qiyas and maqāṣid Al-Sharī'ah to establish the prohibition of khamr since QS. Al-Baqarah/2:219, while Ibn al-'Arabi sees the prohibition of khamr as a gradual process that is only finalized in QS. Al-Māidah/5:90-91. This difference in approach has an impact on how Islamic law responds to new alcohol-related issues. In conclusion, both approaches reflect the flexibility and depth of Islamic law in responding to modern social changes, and can be a reference for the formation of fatwas or sharia-based regulations that are more adaptive.